If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1.5(x-4)=3.5x-24
We move all terms to the left:
1.5(x-4)-(3.5x-24)=0
We multiply parentheses
1.5x-(3.5x-24)-6=0
We get rid of parentheses
1.5x-3.5x+24-6=0
We add all the numbers together, and all the variables
-2x+18=0
We move all terms containing x to the left, all other terms to the right
-2x=-18
x=-18/-2
x=+9
| 14x+6=12x-+12 | | 2X^2+20x+750=0 | | y.12+5=-15 | | X^2+20x+750=0 | | X^2+20x+1400=0 | | 5y-2+y-6=-9y+10+6y+12 | | 7-3x=38 | | 3x+32x-1=7(5x+6) | | 7x+17x-7=6(4x+8) | | 5x+25x-4=6(5x+7) | | 6x+12=8x+8 | | 12x+48=96 | | 15.2=2.5x+9.7 | | 3-(8x-5)+(6-7x+3=7x-(5x+9-3) | | 3x+0.5x=12-13.5x | | 3y+4=5y-7 | | f(0)=5(2^0) | | F(x)=-3x2-x+2 | | f(-2)=2(0.4)^-2 | | 500*1.05x=600 | | 8z/4z= | | F(x)=4x2-5 | | 3x2+3x-2=0 | | 6n2=9n | | 5y-2+y-6=-9+10+6y+3 | | 2a+8=17 | | 6(4-t)-(3-4t)=18 | | 3x-14x=15-5 | | Y=171+0.5x | | 24+4x=2x | | 9(x+1)+8=3x+6(3+x | | 28+7w=7 |